MBO based indicator-setting method for promoting low carbon city practice. (September 2021) - Du, Xiaoyun; Shen, Liyin; Wai Wong, Siu; Meng, Conghui; Cheng, Guangyu; Yao, Fuyi
Highlights: Different cities should apply tailor-made indicators for promoting LCC practice. MBO method can help cities set tailor-made indicators to enable their LCC objectives. Cities must consider their local conditions when setting specific LCC objective. The application of proposed method needs the proper understanding of LCC objectives. Abstract: Cities with different development backgrounds and characteristics will set different objectives for promoting low carbon city practice, including overall, dimensional, and executable objectives. Therefore, a method is needed to ensure that the selected indicators are tailor-made and can correspond to objectives. The existing methods for selecting LCC indicators are not objective-based. This paper introduces an innovative method for setting LCC indicators by using the Management by Objectives (MBO) method to enable the achievement of LCC objectives. Two case cities are used to demonstrate the application of the MBO-based indicator setting method. The main conclusion can be drawn from this study as follows. Firstly, different cities should apply different indicators to guide their LCC practice as they have different backgrounds. Secondly, the MBO method can help different cities to set tailor-made indicators to guide their LCC practice towards their LCC objectives. It is emphasized that indicators applicable to different cities should not be selected discriminately. Thirdly, there are three basic procedures in applying the MBO based indicator setting method, namely, identification of the overall LCC objectives, decomposition of the overall LCC objectives into the dimensional and executable LCC objectives, and selection of indicators for evaluating executable LCC objectives. The application of the MBO based indicator setting method can help the cities choose a set of indicators most suitable to local conditions to guide the LCC practice towards achieving their LCC objective defined locally.